ANALYSIS OF MARKETING STRATEGY FOR MOBILE VEGETABLE TRADERS IN SUKORAMBI DISTRICT JEMBER REGENCY - Ahmad Sauqi (STIE Mandala Jember, 2021)
In Sukorambi District, many of the people are engaged in the mobile vegetable trading business. The sampling technique uses a multistage sampling technique, the SWOT analysis method by determining the IFAS Matrix, EFAS. From the results of IFAS the strength and weakness factors have a total score of 2.95. Value> 2.5 indicates a strong internal potential. From this it can be judged that the internal potential of the mobile vegetable traders is strong. From the EFAS results, the opportunity and threat factors have a score of 3.59. Because the total score is close to 4.0, it means that this indicates that the mobile vegetable traders respond to the opportunities in an extraordinary way. SO strategy by maintaining the quality of the product being sold. ST strategy by providing the maximum possible service. WO strategy by starting the use of price tagging. WT strategy by improving the quality of packing. Keywords:Strategy;Marketing; Traders; Vegetable Around.